Relationship Quality: Its Antecedents and Consequence in the Context of Retailer-Supplier Relationship in Bangladesh - Aziz, Mohammed Tareque (2012)
Relationship quality plays a very important role in shaping business relationships. Therefore it has become imperative to develop research models to explain relationship quality. This study investigated the influence of antecedent factors such as participation in decision making, communication, termination cost, switching cost and operational cost on retailers’ relationship quality in the context of retailers’ relationships with their suppliers in Bangladesh’s retail industry. This study also investigated the relationship between retailers’ relationship quality and its impact on loyalty towards the suppliers. This study further identified the moderating role of relationship duration on the relationship between relationship quality and loyalty. Data for this study was collected using mail survey from 121 independent retailers in all over the geographic territory of Bangladesh. The study establishes that three antecedent factors namely termination cost, switching cost and operational cost (by order of importance) to have significant relationship with retailers’ relationship quality. Consequently, the study also indicated that retailers’ relationship quality significantly influences their loyalty toward their suppliers. Nevertheless, duration of relationship was able to significantly moderate the relationship between retailers’ relationship quality and their loyalty toward their suppliers.